(untitled) (Eurasian Journal of Philology Science and Education, 2018)
This article is dedicated to metaphorization of bird’s namesand their symbolic importance. Investigating the past of the people and comparing with nowadays, language is one of the most important factors in predicting the future. It is well known that today the basis of some advanced language studies of the anthropocentric paradigm is the culture of tertiary researches «language – society – man», «language – nation – culture». In this article, the first goal is to link human’s mind with the bird’s names. The second goal is the interconnectedness between language, nation and nature. Before discussing the mentioned problems, it is necessary to identify the bird’s namesresearch. Thesebird’s namesdetermine their own place and character in the language units, concepts andin the target system. The peculiarities of any themes and their full discussion are connected with the researches of their unexplored sides. Prior to that, the most important prerequisitesof the topicwere human qualities through the bird’s names, whose connection with human existence had not been the object of re searches.